Solar photocatalytically active, engineered silver nanoparticle synthesis using aqueous extract of mesocarp of Cocos nucifera (Red Spicata Dwarf) - Maria Babu Sumi; Aishwarya Devadiga; Vidya Shetty K; Saidutta M. B. (Journal of Experimental Nanoscience, 2017)
Silver nanoparticles synthesised using aqueous extract of Cocos nucifera (CN) mesocarp were evaluated for their photocatalytic activity under solar irradiation. The silver nanoparticles were synthesised by a green method of harnessing bioactive phytocomponents from the mesocarp of Cocos nucifera. Large-scale application of this process necessitates the manoeuvering of the process parameters for increasing the conversion of silver ions to nanoparticles. Process parameters influencing the morphological characteristics of silver nanoparticles such as precursor salt concentration and pH of the synthesis mixture were studied. The crystalline nanoparticles were characterised using UV-vis spectroscopy, XRD, FTIR, SEM and EDX analysis. CN extract and 5 mM silver nitrate solution at a ratio of 1:4 (v/v) in the synthesis mixture was found to be the optimum. Alkaline initial pH of the synthesis mixture was found to favour the synthesis of smaller sized monodispersed silver nanoparticles. Solar energy was harnessed for the photocatalytic degradation of Malachite green dye using silver nanoparticles obtained through the green synthesis method. Overall process aims at utilisation of naturally available resource for the synthesis of silver nanoparticles as well as the degradation of dyes using these nanoparticles, making it useful in the treatment of wastewater.